Motivation to Train East Java Badminton Athletes When Covid-19 Cases are High (The Year 2021) and When Covid-19 Cases Are Low (The Year 2022) - Afif Rusdiawan; Muhammad Labib Siena Ar Rasyid; Farizha Irmawati; Nur Khozanah Ilmah (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2022)
In 2022, cases of covid-19 in Indonesia have decreased compared to 2021. This has led to a loosening of rules related to social activities so that it has an impact on practising badminton. The purpose of this study was to determine the motivation to train East Java badminton athletes in 2021 and 2022. This study used a quantitative descriptive approach. The research subjects were badminton athletes, both male and female, who were included in the age group of teenagers, cadets and adults who were in 10 badminton clubs in 9 districts/cities in East Java Province. The research instrument used a motivational questionnaire that was validated by expert judgements with a total of 19 questions and 6 questions about the frequency, intensity, and duration of exercise. Data collection was carried out 2 times in June 2021 and March 2022 using an online google form. Data analysis used descriptive tests and paired t-tests using SPSS 20 software. The results showed that the motivation to train East Java badminton athletes was dominant in the moderate category with a percentage of 47.06% in 2021 and a percentage of 38.82% in 2022. The results of the t-test Pairs also show that there is a significant difference in motivation to train East Java badminton athletes between 2021 and 2022 on all indicators. The conclusion is that the motivation to train East Java badminton athletes in 2022 is better than in 2021.